Do Police Make Too Many Arrests? The Effect of Enforcement Pullbacks on Crime - Sungwoo Cho; Felipe Gonçalves; Emily Weisburst (Institute of Labor Economics (IZA), 2021)
Do reductions in arrests increase crime? We study line-of-duty deaths of police officers, events that likely impact police behavior through increased fear but are unlikely to directly impact civilian behavior. Officer deaths cause significant short-term reductions in all arrest types, with the largest reductions in arrests for lower-level offenses. In contrast, we find no evidence of an increase in crime or a change in victim reporting through 911 calls. There is also no apparent threshold of arrest decline beyond which crime increases. Our findings suggest that enforcement activity can be reduced at the margin without incurring public safety costs.
Keywords: J15; J18; K42; 330; policing; crime; deterrence; broken windows; Ferguson effect; community trust